Analysis Analysis of Bank Perekonomian Rakyat (BPR) Failures And Implications For Financial Sustainbility - Ashari, Hasan; Supranata, Mardani; Yulistiani, Tiara (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to identify the factors causing the failure of rural banks (BPR) in Indonesia and formulate financial sustainability strategies. Using survey methods and descriptive analysis, it was found that BPR failures were caused by a combination of internal and external factors. Dominant internal factors include poor asset quality with a non-performing loan (NPL) ratio above the threshold, weak governance, ineffective internal supervision, limited core capital, weak risk and compliance management, low human resource competency, and unstable financial performance. External factors include poor public reputation, delays in digitalization, and difficulties in industry consolidation. Strategies include strengthening governance, meeting minimum core capital requirements, improving asset quality through prudent credit analysis, BPR digitalization, strengthening human resources through certification and training, and industry consolidation. This study contributes by linking the analysis of BPR failure factors with the concept of financial sustainability, thereby strengthening the stability and role of BPRs in promoting national financial inclusion.